Convenience and Satisfaction Count: Exploring the Experience and Product Diversity on Repurchase Intention at Cold ‘N Brew, Medan - Pasaribu, Timothy Robin; Kaban, Lila Maria (Universitas Pelita Harapan, 2024)
The study investigates the influence of customer experience, product diversity, and perceived convenience on repurchase intention, using customer satisfaction as a mediating variable, in the context of Cold ‘N Brew coffee shop. As global and local brands focus on innovation and customer engagement, coffee shops in Indonesia face profitability challenges, with nearly 20% failing within two years. The rapid growth of the coffee shop industry has led to intense competition, making customer retention crucial. Using a quantitative approach and SEM-PLS analysis, the research analyzes 160 responses from customers who have visited Cold ‘N Brew in Medan, Indonesia at least twice a year. The findings indicate that customer experience positively influences satisfaction, it does not directly influence repurchase intention. In contrast, product diversity and perceived convenience positively influence both satisfaction and repurchase intention, with satisfaction serving as a mediator for the influences of customer experience and perceived convenience but not for product diversity. The study offers insights for Cold' N Brew and similar businesses, emphasizing the importance of enhancing customer experience, a strategic emphasis on product diversification and enhanced convenience is essential for Cold 'N Brew, Medan to improve customer repurchase intention. The consumer experience will be optimized, and the quality of service will be enhanced, fostering greater loyalty. Furthermore, to attract a broader customer base and remain based on evolving consumer preferences, it is essential to invest in product innovation and enhance service accessibility. This research provides actionable strategies to improve customer satisfaction in a competitive market. This research provides actionable strategies to improve customer repurchase intention in a competitive market.